2022
DOI: 10.1108/pijpsm-04-2022-0050
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based policing and police receptivity to research: evidence from Taiwan

Abstract: PurposeThis paper aims to investigate how evidence-based policing (EBP) is understood by police officers and citizens in Taiwan and the influence of police education on police recruit's receptivity to research evidence in policing.Design/methodology/approachThe study uses a cross-sectional design that includes Taiwanese police officers (n = 671) and a control group of Taiwanese criminology undergraduate students (n = 85). A research instrument covering five themes is developed, and after a pilot test the final… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
(100 reference statements)
1
1
0
Order By: Relevance
“…These findings are consistent with the longitudinal studies that found that academy training, rather than operational experiences, had a greater (negative) impact on officer attitudes and behaviours (Catlin & Maupin, 2004;Fildes et al, 2017). This significant change during police training and non-change during police fieldwork might be explained by both the socialisation process in academy training (Chappell & Lanza-Kaduce, 2010;Conti, 2011) and the similarities of organisational norms and culture in training/working context between CPU and Taiwanese police organisations (Lin et al, 2022). The socialisation process in the CPU entails stripping recruits' old civilian identity via imposing a series of degradations and channelling them towards the police occupation that is characterised by the 'formal, mechanical and arbitrary bureaucratic features' (Chan, 2003;Van Maanen, 1974, p. 88).…”
Section: On the Stages Of Police Socialisationsupporting
confidence: 87%
See 1 more Smart Citation
“…These findings are consistent with the longitudinal studies that found that academy training, rather than operational experiences, had a greater (negative) impact on officer attitudes and behaviours (Catlin & Maupin, 2004;Fildes et al, 2017). This significant change during police training and non-change during police fieldwork might be explained by both the socialisation process in academy training (Chappell & Lanza-Kaduce, 2010;Conti, 2011) and the similarities of organisational norms and culture in training/working context between CPU and Taiwanese police organisations (Lin et al, 2022). The socialisation process in the CPU entails stripping recruits' old civilian identity via imposing a series of degradations and channelling them towards the police occupation that is characterised by the 'formal, mechanical and arbitrary bureaucratic features' (Chan, 2003;Van Maanen, 1974, p. 88).…”
Section: On the Stages Of Police Socialisationsupporting
confidence: 87%
“…However, the way jingshen education is conducted on the ground involves close control of routine activities, discipline, group punishments, ritualistic concerns for details, and repetitive exercises (e.g. drill, recitation) (Adlam, 2002;Cao et al, 2015;Lin, 2020). This education puts recruits under intense surveillance where their HR are often restricted.…”
Section: The Comparison Between Police Education and Criminology Prog...mentioning
confidence: 99%